Correlation of the maximum shear stress with micro-mechanisms of ductile fracture for metals with high strength-to-weight ratio. (October 2018) - Lou, Yanshan; Yoon, Jeong Whan; Huh, Hoon; Chao, Qi; Song, Jung-Han
Highlights: Mechanisms of ductile fracture is investigated experimentally in the wide range of loading conditions from compressive upsetting to the tension of notched specimens for two lightweight metals of DP980 (t1.2) steel sheets and a bulk aluminum alloy of AA7075. All the specimens tend to fail along the direction of the maximum shear stress in various loading states of plane strain compression, uniaxial compression, shear, uniaxial tension and plane strain tension. Fractured voids elongate along the direction of the maximum shear stress for all specimens with the stress triaxiality ranging from negative in compression to 0.57 in the plane strain tension. The experiments of DP980 and AA7075 reveal that ductile fracture takes place along the direction of the maximum shear stress in the wide loading conditions of compressive upsetting, shear, uniaxial tension, and plane strain tension with stress triaxiality below 0.6. Effect of the maximum shear stress must be correctly coupled in modeling of ductile fracture in these loading conditions. Abstract: Mechanisms of ductile fracture are investigated experimentally in a wide range of loading conditions from compressive upsetting to the balanced biaxial tension for two metals with high strength-to-density ratio of DP980 (t1.2) steel sheets and a bulk aluminum alloy of AA7075. Specimens are carefully designed to achieve various loading conditions from shear at low stress triaxiality to the balanced biaxial tension at high stress triaxiality for DP980, while both tensile and compressive tests are conducted for AA7075. Fractured specimen surfaces are analyzed macroscopically focusing on their relations with the maximum shear stress. It is observed that all the specimens tend to fail along the direction of the maximum shear stress in various loading states of plane strain compression, uniaxial compression, shear, uniaxial tension, plane strain tension and the balanced biaxial tension. Scanning electron microscope analyses of fracture surfaces are also conducted to explore the underlying mechanism of void coalescence since coalescence of voids is viewed as the last step of ductile fracture after nucleation and growth of voids. It is noted that fractured voids elongate along the direction of the maximum shear stress for all specimens with the stress triaxiality ranging from about −0.57 in compression to 0.67 in the balanced biaxial tension. The experiments of DP980 and AA7075 reveal that ductile fracture takes place along the direction of the maximum shear stress in the wide loading conditions of compressive upsetting, shear, uniaxial tension, plane strain tension and the balanced biaxial tension with stress triaxiality below 0.67. Thus, ductile fracture is expected to be governed by the maximum shear stress in these wide loading conditions of compression, shear and tension. It is suggested that effect of the maximum shear stress must be correctly coupled in modeling of ductile fracture in these loading conditions with uncoupled and coupled ductile fracture criteria. Graphical abstract: Shear fracture takes place in wide loading conditions of tension, shear and compression.Image, graphical abstract